Estrutura organizacional, orientações para exploitation e exploration e tipos de inovações em institutos de pesquisa e desenvolvimento tecnológicos - Franklin, Marcos Antonio (2011)
This study examines how the organizational structure, mechanical or organic, and guidelines for exploitation and exploration of organizational knowledge can explain the innovations in technology research and development institutes (R & D),focused on products and services related to the Internet, software, hardware, telecommunications (Telecom), information technology (IT) and automation. This study aims to characterize and classify these institutes, according to the models and guidelines adopted at the organizational knowledge. For this, the research has two phases: the first one, a qualitative phase and the second a quantitative phase. The qualitative phase used a semistructured script in four case studies, two cases of national institutes, one private institute and the other a public one, and two private multinational institutes situated in Brazil. For data analysis, we adopt the content analysis, analysis of the dimensions and non-participant observation. Based on the findings of this phase, we carried out the quantitative phase, through the application of a questionnaire to the whole population of 44 R & D institutes, however, only 17 of those institutes respondend. This questionnaire is structured with closed question, and it had incorporated a set of assertions measures, using a Likert scale with seven points. Thie analysis presented is descriptive and it was supplemented with secondary data, by searching the website of these 17 institutes. Therefore, the analysis adopted the technique of data triangulation in order to obtain more reliable results. The results revealed a predominance of organic model in 19 of 21 of the institutes studied, using both steps. However, it appears that, despite the strong orientation towards the organic model, there are elements of the mechanical model: the ability to combine bureaucracy without loosing the necessary flexibility. Two of the institutes have not demonstrated the mechanical configuration combining ability, i.e., the base is the bureaucracy, standardization, formalization and specialization. Whereas guidelines for exploitation and exploration is possible to identify and conclude that the institutes tend to have guidelines for exploration, however, some institutes show focus on exploitation, such as the relative efficiency of the processes and standard work routines. Of the four propositions for this stage of the research institutes in 14 were confirmed and ratified the findings of the qualitative phase. Regarding the classification of the 21 institutes surveyed, it can be stated that the focus is mainly on services and products. With regard to the vocation of the institutes, eleven reveal themselves facing R & D and radical innovations and incremental. However, for nine of these institutes it is possible to affirm that the vocation is D, development. The contribution of this thesis for the academic point of view, reveals that when discussing the role of models of organizational structures and guidelines for exploration and exploitation in search of possible lag between theory and application. The contribution for the business standpoint is that to understand how these factors are fundamental to the development of innovation and competitiveness. It is assumed that these factors may have implications on the performance and the economic viability of the R & D Institutes, since innovation is its business.